PRECEDE-PROCEED MODEL DALAM MENENTUKAN POLA KONSUMSI ULTRA-PROCESSED FOOD PADA MAHASISWA - Fitri, Ummatul; Arumsari, Imas; Ningtyas, Luthfiana Nurkusuma (ARGIPA (Arsip Gizi dan Pangan), 2024)
Frequent consumption with large portions of ultra-processed food could increase the risk of death from degenerative diseases, which can be understood through the PRECEDE-PROCEED model theory in determining factors that influence ultra-processed food consumption patterns in adolescents. This research aimed to determine the relationship between knowledge related to ultra-processed food, exposure to food product advertisements, and peer influence with the consumption patterns of ultra-processed food among young adults. The independent variables in this study were knowledge related to ultra-processed food, exposure to food product advertisements, and peer influence, while the dependent variable was the consumption pattern of ultra-processed food. The research method employed was quantitative research with a cross-sectional design. Data were collected through interviews and questionnaire completion from 158 subjects. Sampling was determined using accidental sampling techniques. Data analysis in this study was conducted with bivariate analysis using chi-square statistical tests. The results indicated that 83.5% of the subjects consumed ultra-processed food frequently, with the analysis yielding a p-value of 0.204 for knowledge related to ultra-processed food, a p-value of 0.203 for exposure to food product advertisements, and a p-value of 0.135 for peer influence. It can be concluded that there was no significant difference in proportions between knowledge related to ultra-processed food, exposure to food product advertisements, and peer influence on the consumption pattern of ultra-processed food among university students.